Significance of the auditory meatus inferior wall cartilage in the surgical treatment of congenital first branchial cleft anomalies in children - Bo Yu; Bin Xu; Jing Bi; Lulu Yu; Ruiyang Zhu; Yong Fu (BMJ Publishing Group, 2023)
Objective To investigate the clinical significance of the inferior wall cartilage of the auditory meatus in surgical treatment of congenital first branchial cleft anomalies (CFBCAs) in children.Methods Twenty children diagnosed with CFBCAs who underwent surgery between December 2018 and June 2022 at our hospital were retrospectively analyzed and classified according to their Work lesion type. The guiding significance of the inferior wall cartilage in the surgical treatment of CFBCAs was summarized by investigating the adjacent relationships of the surgical lesions with the external auditory canal and facial nerve.Results Of the 20 patients, 16 were classified as Work type I and 4 as Work type II. The lesions were adjacent to the inferior wall cartilage of the auditory meatus in all children. Work type I lesions were located in the upper lateral aspect and were not adjacent to the facial nerve. Work type II lesions were located in the inferior-medial region of the facial nerve. The lesions were completely resected in all children. One patient experienced recurrence 3 months postoperatively because of a residual endochondral fistula. No patients developed facial paralysis or other complications.Conclusions The inferior wall cartilage of the auditory meatus may help to the identify the initial lesion of the CFBCAs and can be regarded as a guiding anatomical structure. These lesions can be completely resected. For resection of Work type II first branchial cleft lesions, the surgical incision can be narrower, and can be precisely positioned with the assistance of endoscope.